Wind and solar power systems : design, analysis, and operation - Patel, Mukund R.; Beik, Omid (2021)
"This book provides technological and socio-economic coverage of renewable energy. It discusses wind power technologies, solar photovoltaic technologies, large-scale energy storage technologies, and ancillary power systems. In this new edition, the book addresses advancements that have been made in renewable energy: grid-connected power plants, power electronics converters, and multi-phase conversion systems. The text has been revised to include up-to-date material, statistics, and current technology trends. Three new chapters have been added to cover turbine generators, AC and DC wind systems, and solar power conversion. Discusses additional renewable energy sources, such as ocean, special turbines, etc., Covers system integration for solar and wind energy. Presents emerging DC wind systems. Includes coverage on turbine generators. Updated sections on solar power conversion. It offers students, practicing engineers, and researchers a comprehensive look at wind and solar power technologies. It is designed as a reference and can serve as a textbook for senior undergraduates in a one-semester course on renewable power or energy systems"--
Includes bibliographical references and index.
Keywords: Wind power plants; Solar power plants; Photovoltaic power systems